2018
DOI: 10.1007/s12034-018-1676-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations into viscosity, pH and electrical conductivity of nanofluid prepared from palm kernel fibre and a mixture of water and ethylene glycol

Abstract: Extensive research has been carried out on the synthesis and applications of nanofluid produced from metals, nonmetals and their oxides. However, little or no attention has been paid to bio-based nanoparticles. The need for the use of bio-based nanoparticles and bio-based nanofluids is imperative to mitigate over-dependence on toxic synthetic nanoparticles. This idea is also in line with renewable and sustainable developmental goals. Moreover, bio-based materials like palm kernel fibre (PKF) constitute environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Presently, ionic base fluids are yet to be investigated concerning the HNFs application focus of this review. In addition, green base fluids and green HNFs under the auspices of green, efficient, and sustainable HNFs are futuristic experimental undertakings in this research direction as very few studies have been carried out on the thermophysical and convective properties [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Challenge and Research Outlookmentioning
confidence: 99%
“…Presently, ionic base fluids are yet to be investigated concerning the HNFs application focus of this review. In addition, green base fluids and green HNFs under the auspices of green, efficient, and sustainable HNFs are futuristic experimental undertakings in this research direction as very few studies have been carried out on the thermophysical and convective properties [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Challenge and Research Outlookmentioning
confidence: 99%
“…In the last few years, studies have emerged on investing in the properties of green nanofluids prepared from the powder form of plant species like banana fiber, mango bark, and palm kernel fiber. [18][19][20] Nevertheless, research on green nanofluids is in the early stages of progress. It is challenging to create them from non-toxic and sustainable resources since additional research is required to determine the suitability, sustainability, and accessibility of the resources.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they compared the PG and water blend at the same proportions and found an increase in TiO 2 properties by 12.6% and in SiO 2 properties by 7.2%. In the last few years, studies have emerged on investing in the properties of green nanofluids prepared from the powder form of plant species like banana fiber, mango bark, and palm kernel fiber 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivity and viscosity of nanofluids have received good attention theoretically and experimentally in order to understand the underlying causes of the inconsistent enhancements [1][2][3][4][5][6]. Hong et al [7] showed that agglomeration formation is one of the underlying factors that affect the enhancement value of nanofluids.…”
Section: Introductionmentioning
confidence: 99%